The Caliph’s Verse at The Reception of The Ahmadiyya Congregation in Kudus - Mohammad Salahuddin Al-Ayyuubi (Jurnal Ilmu Agama: Mengkaji Doktrin, Pemikiran, dan Fenomena Agama, 2023)
From several Qur’anic verses concerning the caliph, Surah An Nur Verse 55 is believed by every Ahmadiyya Congregation as the basis for ratifying the concept of an Islamic caliphate. This qualitative field research aims to describe the reception of the Ahmadiyya Congregation in Kudus to the Caliph’s Verse, including the factors behind the reception and the form of the reception they carried out. Data collection was carried out in Kudus district by means of observation, interviews and documentation. In the field data analysis, the Miles and Huberman model was used through the stages of data reduction, then data presentation, followed by drawing conclusions and verification. From this research it is known that the meaning of the Caliph according to the Ahmadiyya Congregation in Kudus is spiritual leadership for the whole world which must be obeyed in order to achieve the glory of Islam and peace as promised by Allah in Surah An Nur Verse 55 while at the same time believing in the truth of the Ahmadiyya Caliphate which will last until the end of time. The reception was motivated by ideological factor which resulted in deviations in interpretation due to fanaticism towards the teachings that were integrated in the interpretation of the Qur’anic verse. This reception is classified as an intellectual reception in the context of passive and active reception of context, and manifests itself in the realm of hermeneutical, aesthetic and practical reception.